Determinants of nutritional status and lifestyle diseases among middle aged working women - Siji M.S (Department of Community Science, College of Horticulture, 2019)
Middle age is a phase of transition from young age to old age. Along with the psycho-physiological transitions of midlife, many chronic diseases like hypertension, diabetes, osteoporosis, cardiovascular problems, obesity etc. increase when women reach their middle age. The hectic schedule of balancing home, work, along with balancing social and personal needs could lead middle aged working women to ignore their health until their health problems become chronic or fatal. The present investigation entitled “Determinants of nutritional status and lifestyle diseases among middle aged working women” was undertaken to assess the nutritional status, work stress, standard of living and prevalence of life style diseases among middle-aged working women. Risk factor index, correlates and prediction formulae for the determinants of nutritional disorders and lifestyle diseases were also derived. The study was conducted among a total of 360 middle aged (45-55 years) working women of Thiruvananthapuram district. Forty middle aged working women were selected from each of the nine divisions of occupation as envisaged in the National Classification of Occupation (NCO, 2004). The nine occupational division includes (D1)-senior officials, (D2)-professionals, (D3)-technicians, (D4)-clerks, (D5)-service workers, (D6)-agriculture & fishery workers, (D7)-craft workers, (D8)-machine operators and (D9)-construction workers. The In depth investigations were conducted among 30 per cent of the respondents (n=108) identified to be the most vulnerable. The socio-economic status assessment showed that nuclear family system was predominant. High variability in educational status, socio-economic status and housing conditions were observed among the occupational categories. Using the baseline data, a modified Standard of Living Index (MSLI) was derived. MSLI is based on 4 dimensions viz. Individual characteristics (2 items), housing conditions (8 items), consumer durables (7 items) and social variables (2 items) with a total of 19 items. Scores were assigned for each variable in ascending order. Based on these scores, respondents were classified into upper, middle and lower standard of living. MSLI assessment revealed that more than 75 per cent of the respondents in D1, D2, D3, D4 and D8 had medium to high SLI. While a major proportion of respondents from D5, D6, D7 & D9 belonged to low SLI. Nutritional status assessment revealed higher prevalence of abdominal obesity (95.6 per cent), elevated body mass index (65.6 per cent), waist - hip ratio (WHR) (81.7 per cent) and body fat percent (96.9 per cent) among middle aged women irrespective of the occupational class difference. An assessment of household stress, work stress and psychological distress was studied, by standardising the stress scale. The significant item-total correlation and high Cronbach’s alpha confirms the validity and reliability of the developed stress index (SI). The application of the stress index revealed moderate to high stress prevalence among the major proportion of the respondents. Statistical analysis confirmed the inter-dependence of stress and occupational divisions. Physical activity (PA) was assessed using the Global Physical Activity Questionnaire, version 2 (WHO, 2013). Metabolic equivalent (MET) scores were used to classify the physical activity of the respondents. It was observed that more than 60 per cent of the respondents from all the occupation divisions were inactive or less active. An exception was noted in D9 where 60 per cent of construction workers were classified as active. Physical activity and occupational divisions were statistically dependent on each other. The physical work capacity of the respondents revealed that majority of the middle aged women had below average work capacity (45%). The vital capacity of the respondents were measured using the peak expiratory flow rate (PEFR) and found that majority of the respondents had moderate (57%) to poor (36%) lung capacity. Medical camps were organized to assess the occurrence and prevalence of lifestyle diseases. Health problems related to neurological, musculo-skeletal, gastro-intestinal and urological complaints were reported by majority of the respondents. Prevalence of lifestyle diseases viz. diabetes, hypertension and hypercholesterolemia was 73 per cent and prevalence of combination of two of the lifestyle diseases was 31 per cent. More than half of the study population had raised fasting blood sugar (55.6%), total cholesterol (76.9%), systolic blood pressure (54%) and diastolic blood pressure (72.2%). Anemia was observed in 21 per cent and calcium deficiency in 15 per cent of the sample. More than 60 per cent of the respondents were osteopenic indicating low bone mineral density and increased risk of fractures. More than 40 per cent of the respondents attained menopause with almost 50 per cent experiencing moderate menopausal symptoms. Prevalence of lifestyle diseases was statistically independent of the occupational status and SLI of the respondents. Majority of the respondents were aware of their lifestyle diseases and were also undergoing regular treatments. Inadequacy in the intake of quality foods mainly pulses, milk, roots and tubers, leafy vegetables, other vegetables and fruits were noticed among all the occupational divisions. A diet quality index (DQI) was formulated in the study aiming at the qualitative assessment of middle aged women’s diet and to assess dietary risk factors of lifestyle diseases using the Indian dietary guidelines and recommendations of international dietary indices. Scores were assigned to the four dimensions included in the DQI viz. dietary adequacy variables (45 scores), dietary moderation variables (15 scores), healthy dietary practices (20 scores) and dietary diversity variables (20 scores) with a maximum score of 100. Based on the DQI scores, respondents were categorized to very poor, poor, average, good and excellent diet quality. More than half of the middle aged women from all occupation divisions had an average DQI. DQI was dependent on occupational status. Higher DQI scores showed significant negative correlation with waist circumference and prevalence of lifestyle diseases. Lifestyle disease incidence was positively correlated with elevated waist circumference and stress index. Significant negative correlation was observed between lifestyle disease prevalence and physical activity. All anthropometric variables were highly correlated with each other. As revealed by the multinomial logistics regression analysis, the elevated WC, WHR, lack of PA and low DQI are the significant determinants contributing to the occurrence of one of the lifestyle diseases. The odds percentages were 48%, 99%, 50% and 71% respectively. The elevated BMI, WC and WHR had significantly higher probability for further encountering another lifestyle disease as per the odds percentage were 52%, 47.8% and 61.5% respectively. The significant predictors leading to the final stage of developing a high susceptibility towards all the three lifestyle diseases as per the odds percentage were elevated WC (48%), body fat per cent (53%), WHR (99%) and high SLI (49%). Principal Component Analysis was carried out for generating a minimum data set of risk factors contributing to nutritional disorders and lifestyle diseases. The five significant risk factor dimensions identified in the present study were nutritional anthropometry, raised blood pressure, physical inactivity factors, adiposity factors and psychological & diet quality factors with total of 12 risk factor items/variables. Accordingly a risk factor scale was developed. The application of the developed risk factor scale among the respondents revealed that 39 per cent had moderate risk, 31 per cent had low risk and 30 per cent had high risk for developing lifestyle diseases and nutritional disorders. Construction workers showed the highest risk factor index and machine operators showed least risk factor index for lifestyle diseases. The study gave an insight to the nutrition transition that middle aged working women are undergoing. Alarmingly high prevalence of overweight and obesity coupled with a high burden of life style diseases was observed in the study. Intervention strategies for early detection and modification of risk factors identified in the study viz. unhealthy diet, sedentary life style, household as well as work life stress, lack of regular physical activity, poor fruit and vegetable consumption, abdominal or central obesity and high body fat should be advocated both at community and household level. Adoption of cost-effective measures for the prevention and control of life style diseases such as dietary modification, regular physical activity and life style changes should be encouraged throughout women’s lives to promote healthy midlife and ageing. The tools and indices developed in the study will be useful for various epidemiological studies and can be applied to the general population. These tools will provide an updated measure to evaluate the socio-economic, health and nutritional status of middle aged women. The study strongly recommend to consider middle aged women as vulnerable population and requires policy attention and age specific nutritional intervention programmes.